Brain drain and brain gain the global competition to attract high-skilled migrants - Boeri, Tito. (Oxford : Oxford University Press, 2012)
This volume considers the global competition to attract talents and the brain gain and brain drain associated with high-skilled migration. Part I provides an overview of immigration policies specifically aimed at selecting and attracting skilled workers. Part II looks at the consequences of brain drain for sending countries.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Brain drain; Labor mobility; Skilled labor -- Recruiting